Mathematical modeling of treating water in vertical settlers - Biliaiev, N. N.; Nagornaya, H. K. (Science and Transport Progress, 2012)
The 2D-numerical model was developed and used to simulate the pollutant transfer in the vertical settler. The model is based on the numerical integration of the K-gradient transport model and the model of the potential flow. The results of numerical experiment are presented.